I survived : the Black Death, 1348 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2024)
"The Black Death was a pandemic of unimaginable proportions, taking the lives of 75 - 200 million people worldwide. Lauren Tarshis's story of one girl surviving the plague pulses with terror, action, and hope. The deadliest disease in the history of the world... Elsie dreams of becoming a brave warrior like her father, who is an archer fighting in England's war against France. But life isn't fair in 1348 Europe. Peasant girls like Elsie can't be archers or knights or anything exciting. Then one day in the forest, Elsie and her best friend, Humphrey, discover a chest filled with stolen treasures--and a dangerous secret. At last Elsie has a chance to prove that she's as brave as any knight. Little does she know that a deadly illness -- the Black Death--has begun its attack on England. It's already killed millions around the world. And now it's come for Elsie"--Provided by the publisher.